Asymptotic multiple scale method in time domain : multi-degree-of-freedom stationary and nonstationary dynamics /: multi-degree-of-freedom stationary and nonstationary dynamics. (2022) - Awrejcewicz, J (Jan); Starosta, Roman; Sypniewska-Kamińska, Grażyna
No abstract available